2019
DOI: 10.1002/ep.13173
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic combination of H2Zr1PW12O40 and Sn‐Beta as potential solid acid catalyst for direct one‐step transformation of glucose to ethyl levulinate, a biofuel additive

Abstract: Ethyl levulinate (EL) has found wide applications as chemicals and biofuel additives. Efficient catalytic conversion of abundantly available glucose to ELs over solid acid catalyst having optimum Brønsted (B) and Lewis (L) acidity is highly appreciated. Present work demonstrated, direct one‐step synthesis of EL from glucose over synergized Brønsted (H2Zr1PW12O40) and Lewis (Sn‐Beta) acid catalyst. H2Zr1PW12O40 is prepared by exchanging H+ of tungstophosphoric acid (H3PW12O40‐heteropolyacid) with Zr, improves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This indicated that a synergistic effect between ZrO 2 and Al 2 O 3 produced obvious B acid sites. Studies have shown that B acid and L acid co‐catalysts significantly increase the yield of EL 70 . Dai et al .…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that a synergistic effect between ZrO 2 and Al 2 O 3 produced obvious B acid sites. Studies have shown that B acid and L acid co‐catalysts significantly increase the yield of EL 70 . Dai et al .…”
Section: Resultsmentioning
confidence: 99%
“…This effect occurred because the alcoholysis of the cellulose generated a large amount of humus that was deposited on the surface of the catalyst, so that the catalytic activity decreased. 54 At 180 °C, the yield of EL continued to increase along with the reaction time, although the yield after 6 h was only increased by 0.1 to 42.6 mol% compared with that after 5 h. These results are attributed to the need for high temperatures to induce complete depolymerization of the cellulose. However, with the rapid depolymerization of the cellulose, a large amount of humus would be formed, resulting in decreased activity.…”
Section: Effects Of Reaction Temperature and Timementioning
confidence: 88%
“…This occurred because, with the increased number of active sites, the amount of reactant species and the quantity of active sites reached an optimal level, beyond which the addition of more active groups hindered contact between the reactants and the substrate, thus reducing the yield. 54 Nandiwale et al 56 used the solid acid HPW/MESO-HZ-5 to catalyze the transformation of furfuryl alcohol to EL. When the HPW loading was increased from 5 to 15 wt%, the EL yield increased from 14.0 to 24.0 mol%, while a further loading increase to 20 wt% actually resulted in a slight decrease in yield.…”
Section: Effects Of Reaction Temperature and Timementioning
confidence: 99%
“…The catalyst also demonstrated better catalytic activity compared to other carbon-based solid acids (HTC-400-S and AC-Fe-SO 3 H), possibly due to superior structural properties and B-and L-acid synergies.Therefore, catalyst 300-AC-Cr-SO 3 H is an efficient catalyst for the alcoholysis of glucose. Glucose ZrY6(0.5) 180 °C, 3 h 35 [12] Glucose Sn-SBA-15 160 °C, 20 h 34.9 [25] Glucose Amberlyst-15 160 °C, 5 h 24 [26] Glucose H-USY(6) 160 °C, 20 h 49 [27] Glucose* 4-HPWFe-MMTSi 180 °C, 1 h 22.5 [28] Glucose* HTC-400-S 200 °C, 2 h 37 [13] Glucose AC-Fe-SO…”
Section: Catalytic Performance For Glucose Ethanolysismentioning
confidence: 99%